2-Cys Prx plays a critical role in scavenging H2O2 and protecting photosynthetic function in leaves of tobacco seedlings under drought stress. Issue 1 (1st January 2019) - Zhang, Hui-Hui; Xu, Nan; Teng, Zhi-Yuan; Wang, Jun-Rui; Ma, Songliang; Wu, Xuye; Li, Xin; Sun, Guang-Yu
ABSTRACT: Drought stress led to a decrease in PSII photochemical activity in tobacco leaves and the blockage of electron transfer, especially from Q A to Q B on PSII acceptor side. In addition, drought stress caused a dramatic increase in H2 O2 and MDA contents. However, the overexpression of 2-Cys Prx significantly reduced the H2 O2 accumulation in tobacco seedlings and alleviated the degree of oxidative damage under drought stress. It also improved stomatal limitation and net photosynthetic rate of tobacco seedlings and reduced its PSII photoinhibition under drought stress which promoted the ability of PSII electron transfer.